Cultural Integration of Chinese Symbols in Salaf Pesantren - Muhammad Aji Nugroho (Journal of Pesantren and Diniyah Studies, 2026)
This study is motivated by the presence of Chinese-style architecture at Pondok Pesantren Annasiha Salatiga, which continues to preserve the traditional salaf pesantren educational system and Javanese santri culture. This phenomenon reflects a unique cultural encounter between Islam, Javanese tradition, and Chinese culture within the educational space of the pesantren. The study aims to analyze the symbolism of Chinese architecture, the construction of Javanese identity, and the practice of religious moderation within the pesantren environment. This research employs a descriptive, qualitative approach, drawing on the perspectives of cultural anthropology and architectural semiotics. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that Chinese architectural elements, including curved roofs, Chinese-style gates, ornaments, and symbolic colors, are reinterpreted within the Islamic and Javanese traditions of An-Nasiha Salaf Pesantren. Their integration with Javanese cultural values fosters cultural acculturation, multicultural awareness, tolerance, and religious moderation, contributing to the formation of an inclusive and adaptive Islamic identity. This study recommends further development of pesantren studies focusing on cultural perspectives and architectural symbolism as part of broader discussions on Islam Nusantara and multicultural Islamic education.